Induction healing of fatigue damage in asphalt test samples. (15th January 2015) - Menozzi, Alessandro; Garcia, Alvaro; Partl, Manfred N.; Tebaldi, Gabriele; Schuetz, Philipp
Highlights: We damage asphalt test samples with indirect fatigue tests. We heal the test samples with induction heating. There is an optimum damage level for healing. Asphalt test samples extend their lifetime by 30%. Bitumen suffers ageing damage during induction heating. Abstract: To promote asphalt self-healing, asphalt mixture can be heated via induction heating. This technique consists in adding electrically conductive and magnetically susceptible particles (e.g. steel) into asphalt mixture; then, with the help of an induction heating machine asphalt mixture can be heated. When the temperature of asphalt mixture is above a certain threshold (between 30 °C and 70 °C, depending on the type of bitumen), microcracks start self-healing. Induction healing has been previously demonstrated for repairing asphalt mixture test specimens broken in two pieces, but this technique has never been used for repairing microcracks caused by fatigue damage. In this article, the optimum moment and temperature needed to repair asphalt mixture under fatigue damage have been experimentally determined. With this purpose, Marshall test specimens have been damaged through indirect tensile fatigue tests and healed via induction heating. Finally, damage and healing have been quantified through computed tomography scan tests.